Elevator Safety Monitoring System Based on Internet of Things - Zihan, Ming; Shaoyi, Han; Zhanbin, Zhang; Shuang, Xia (International Journal of Online and Biomedical Engineering (iJOE), 2018)
In view of the frequent occurrence of elevator accidents, an elevator safety monitoring system based on the Internet of things (IOT) was designed. First, the requirements of elevator safety monitoring system were analyzed in terms of function and performance, andthe feasibility of the system was evaluated from perspectives of demand, technology, and practical operation. The design scheme of the system was then presented, which combined the Brower/Server (B/S) and Client/Server (C/S) architectures. As the client of the command and control center, the front-end monitoring system communicated and interacted with it and used the standard real-time transport protocol (RTP) for transmission. Finally, the elevator safety monitoring system was implemented. The test showed that the function and performance of the proposed elevator safety monitoring system achieved the designed target of the system and had practical application value.